The World of Jak Smyrl : South Carolina Artist, Journalist, Cartoonist - Inabinet, Joan A.; Inabinet, L. Glen (Book collections on Project MUSE., 2020)
"The subject of this biography was himself the grand source of information on his life and times. Close ties aside, the authors, having interviewed Jak a number of times for other projects, now recognize that unknowingly they were then also collecting information for his biography. Jak was a source for us in our writing of A History of Kershaw County, South Carolina, University of South Carolina Press, 2011, and a source for Joan (his niece) in compiling a family history"--